The Effect of English Camp Program in Public Speaking of STKIP Al Maksum Students - Muhammad Hassan; Sara Frimaulia; Ega Salsabhyla ZR (LPPM STKIP AL MAKSUM, 2021)
The objective of the research is to improve speaking skill of English House Course students through English camp strategy. This was an pre-experimental research using one group on pre-test and post-test design, the population of this research was the students of English House Course which has 80 students. Because the total number of the population was big enough, the researcher took 20 samples and applied random sampling technique; it means that one class of the population were taken as samples and the data was analyzed into percentage, mean score analyzes and the value of the t-test. The result of the data analyzes shows that the students’ achievement on the pre-test was 71,7 and post-test was 86,1. This shows that English camp is a good strategy in English learning process at the students of English House Course Langkat. After analyzing the data by using the t-test formula, the result of the t-test value (11,86) was greater than t-table value (2,093). This indicated that the hypothesis of research is accepted. There is a significant Influence of English camp program towards the students’ achievement in English learning process. The researcher does English camp in English House Course Langkat Kabupaten Enrekang for five days and it gives positive effect of students’ skill in speaking. All item of learning achievement able to improve the students’ speaking skill. Keywords: Speaking Skill; English Camp